Performance of Agricultural Sector in Bali - Widhianthini, W (KnE Life Sciences, 2022)
Agriculture plays a multifunctional role in a district’s development. Bali is an Indonesian province that uses rustic regions as a gateway to the agricultural sector, which supports the tourism industry. In 2020, this sector was responsible for 15% of Bali’s gross domestic product, ranking second among 17 sectors (the sector of providing convenience, food and drink took the lead at 18%). The purpose of this review was to plan the development typology of the sector and assess the variables causing changes in the agricultural sector’s impact in the Bali region. The investigation was focused on the Bali area, and it was completed with the intention of examining expansions in agrarian land in Bali. Klassen typology and ISM were used in the research. The farming, ranger service, and fisheries areas were placed in quadrant II as a result of this review. According to the ISM analysis, land conversion, reduced water discharge, and the decline in productivity of farmers affect the agricultural sector’s performance in the short term; the budget for the agricultural sector, agricultural subsidies, and the synergy between agriculture and tourism affect the agricultural sector’s performance in the medium term. Meanwhile, the application of new technology, the existence of subak, the marketing system’s orientation, and the strengthening of the agricultural agroindustry are all important long-term factors. As a result, increasing the agricultural sector’s growth can be accomplished by establishing an industry for processing raw materials, integrating regional regulations and awig-awig, and providing appropriate incentives for farmers. Keywords: agricultural sector, the existence of subak, awig-awig